Frailty in elderly patients with chronic kidney disease under conservative treatment - Aline de Sousa Meira; Marcelo Aparecido Batista; Roberta Maria de Pina Pereira; Rosalina Aparecida Partezani Rodrigues; Jack Roberto Silva Fhon; Luciana Kusumota (Rev Rene)
Objective: to assess the frail level of the elderly with chronic kidney disease under conservative treatment.Methods: this is a cross-sectional and correlational study performed with 35 elderly. The frailty was assessed using the Edmonton Frail Scale instrument. A descriptive analysis and Spearman correlation coefficients were performed. Results: the frailty showed a minimal variation of 1 and maximum of 14, with a mean score 7.71 (± 3.10). Women (8.05 ± 3.551) and illiterates (9.57 ± 2.637) showed a higher mean score of frail. By correlating the frail score, a moderate inverse correlation was found with years of study (p=0.033) and moderate positive correlation with some complications (p<0.000). Conclusion: the elderly with chronic kidney disease under conservative treatment showed some frailty degree, the highest levels were correlated with lower education and a higher number of clinical complications.